The Nature of High-Temperature Peaks of Thermally Stimulated Luminescence in NaCl:Li and KCl:Na Crystals - Kuanyshbek Shunkeyev; Shynar Sagimbayeva; Adelya Kenzhebayeva; Zarina Serikkaliyeva (Crystals)
For the first time, thermally stimulated luminescence spectra in the region of high-temperature peaks (up to 770 K) have been measured in NaCl:Li and KCl:Na single crystals (with impurity cations of small ionic radii) exposed to isodose irradiation by X-rays irradiated uniformly. Comparative analysis of these spectra with the spectra of X-ray and tunnel luminescence of the same crystals showed that the luminescence associated with exciton-like formations near impurity cations dominates in all three cases. The formation mechanisms of such bound excitons during a thermal dissociation of complex radiation defects are considered. Integral light sums of high-temperature TSL in NaCl:Li and KCl:Na crystals are significantly higher than that of a standard LiF:Mg, Ti dosimetric crystal (a TLD-100 luminescent dosimeter).